The Effect of Group Counseling with Self-Control Techniques in Reducing Online Gaming Addiction Among High School Students - Defriyanto, Defriyanto; Wibowo, Mungin Eddy; Sugiyo, Sugiyo; Septyanti, Ernest Ceti; Sutoyo, Anwar (Universitas Islam Negeri Raden Intan Lampung, 2025)
This This study aimed to investigate the effectiveness of group counseling services employing the self-control technique in reducing online gaming addiction among tenth-grade students at SMA Negeri 1 Labuhan Maringgai, East Lampung. The research adopted a quantitative approach using a one-group pretest-posttest design. The sample was selected using purposive sampling. Data were collected through a Likert-scale questionnaire, interviews, and documentation. Hypothesis testing was conducted using the Wilcoxon test, which revealed a Z-score of -2.201 compared to a critical value of 1.96, with a significance level of 0.028 < 0.05. These results indicated a significant effect of group counseling with the self-control technique on decreasing the level of online gaming addiction. The findings suggested that group counseling could serve as an effective intervention in addressing online gaming addiction among students.